Students’ Engagement in Learning English during the Practice of Teacher-In-Role - Fatimah Firdaus; Sitti Fatimah (Journal of English Language Teaching, 2021)
The method of teaching is considered as the factors to reach the objectives of learning English of the EFL students in Indonesia. The method of teaching that was used in this research was called Teacher-in-Role. Teacher-in-Role is one of the strategies used in the classroom that involves the use of dramatic activities and performances as strategies within classroom instruction to give more meaningful of students’ life experiences, ideas and issues through imagined situation, with the teacher as facilitator, simulator or an actor on purpose of reaching the learning outcomes. This descriptive qualitative research attempted to find out how the students’ engagement during the practice of Teacher-in-Role (TiR), and also to find out their opinions of using TiR in the classroom. There were 32 students involved in this research. The result of the study showed that the engagement of the student in the classroom during the practice of TiR were in positive nature, from the three indicators; behavioural engagement, emotional engagement, and cognitive engagement. The results showed the students had positive engagement and seemed they had interest during activities in total three meetings of practicing the TiR in English lessons. The perception of the students also gave a positive impact toward the TiR in the classroom. In general the students were having fun and enjoyed the learning process by practicing TiR. Even though some students claimed that they have some difficulties speaking English due to the lack of vocabulary they have.